Effects of type-2 resistant starch (high-amylose maize starch) on the glycemic index of chinese steamed buns and its influence on glycemic response in healthy human subjects - Noraidah Haini; Lee, Jau Shya; Ramlah George @ Mohd. Rosli; Hasmadi Mamat (Elsevier Ltd, 2021)
The incorporation of resistant starch (RS) in food has gained importance to be a good replacement for carbohydrate. This study aimed to determine the effects of resistant starch (RS) known as high-amylose maize starch (HM) as wheat flour substitute in Chinese steamed bun (CSB) formulation on postprandial glycemic response in healthy human subjects. In the single-blind cross-over experimental trial, subjects (female, n=15) consuming 30% HM (HM30) composite CSB had significantly lower postprandial blood glucose response compared with control consuming CSB (without HM) within 2 hours after ingestion of both samples. Compared with control CSB, HM30 produced lower glycemic response with a mean iAUC of 105.2 mmol x min/L. The mean iAUC of control CSB was 186.1 mmol x min/L. The low GI property of HM30 stabilized the blood glucose concentration level and did not cause sudden rapid increase in blood glucose concentration similar to high-GI reference food and medium-GI control CSB.